Femtosecond Laser Backside Ablation of Gold Film on Silicon Substrate - Lei, Shuting; Grojo, D.; Ma, J.; Yu, Xiaoming; Wu, H. (My University, 2016)
Femtosecond laser ablation of gold thin film on the front and backside of silicon substrate is investigated, with backside ablation being the focus and front side ablation for comparison. The experiments are performed using 100 fs pulses delivered through an ultrafast laser source combined with an OPA for wavelength conversion at 1300 nm. We create a single shot ablation matrix by varying focus position and pulse energy. The laser beam is characterized using an IR imaging technique at both the front and backside of the substrate. It is found that the pulse profile experiences little distortion after passing though the 1 mm silicon substrate, despite the high pulse energy used. However, a comparison of the front and back ablation site indicates significant attenuation of pulse energy due to nonlinear absorption. Two types of damage happen depending on laser fluence: ablation and burst. Burst damage is confirmed with finite element simulation. © 2016 The Authors
Citation: Lei, S., Grojo, D., Ma, J., Yu, X., & Wu, H. (2016). Femtosecond Laser Backside Ablation of Gold Film on Silicon Substrate. Procedia Manufacturing, 5, 594-608. doi:10.1016/j.promfg.2016.08.049
Keywords: Au Thin Film; Fem Simulation; Fs Laser; Laser Backside Ablation; Silicon Substrate